Efektivitas Duolingo: Sebagai aplikasi untuk meningkatkan pembendaharaan kosa kata bahasa Inggris bagi pelajar - Ilmi, Rofi' Ul (Maliki Interdisciplinary Journal, 2024)
English is a language that needs to be mastered by students to support broader knowledge. But in reality there are still many students who experience difficulties in mastering vocabulary, especially in terms of memorizing, pronouncing, interpreting and listening. So to overcome this problem, especially by using the Duolingo application as a means of increasing vocabulary in English. This article was created with the aim of knowing the effectiveness of using the Duolingo application in English vocabulary. The results from various sources of the Duolingo application have proven its effectiveness as a learning medium for students.